Reaksi Pasar Keuangan Terhadap Nilai Tukar dan Minyak Dunia - Rasyidin, M; Rizkina, Azka; Saleh, M; Muttaqim, Hakim (TIN: Terapan Informatika Nusantara, 2023)
This research aims to examine the influence of world exchange rates and oil on financial markets in Indonesia from 1993 to 2022. The type of data in this research is secondary data and multiple linear regression analysis methods. That the exchange rate has a positive and significant effect on the financial market in Indonesia, which means that every increase in the exchange rate is followed by an increase in the financial market in Indonesia. World oil has a negative and significant effect on the financial market in Indonesia, meaning that every increase in world oil will reduce the financial market in Indonesia.